Risk factors of renal function deterioration after radical nephroureterectomy for upper tract urothelial carcinoma - Li, Qinghui; Chen, Tan; Zhu, Anli; Zhou, Jie; Zhu, Jiawei (Frontiers in Oncology, 2024)
Background and objectivesTo investigate the risk factors of renal function deterioration after radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC).MethodsA total of 153 patients with UTUC who underwent radical surgery at a high-volume center in China from January 2015 to December 2019 were included in this study. The renal function of all patients was evaluated during follow-up. Besides, these patients were grouped according to postoperative renal function. The risk factors of renal function deterioration included age, sex, body mass index (BMI), T stage, tumor location and size, lymph node invasion, lymph node dissection (LND), surgical margin, tumor histology, lymphovascular invasion (LVI), hypertension, diabetes, hematuria, blood transfusion, hydronephrosis on the affected side, urine specific gravity, creatinine, uric acid, and preoperative glomerular filtration rate (GFR) on the healthy and affected sides. The correlation between risk factors and inclusion indexes was analyzed using univariate and multivariate analyses.ResultsA total of 153 patients were enrolled in this study, and the follow-up continued for 14 (11, 24) months. Acute kidney injury (AKI) was diagnosed in 65 patients in the short-term follow-up after RNU, and renal function deterioration was diagnosed in 52 patients in the long-term follow-up after RNU. The univariate analysis of 65 patients with short-term AKI revealed that there were statistically significant differences in preoperative hydronephrosis, hypertension, urinary protein, tumor size, preoperative Hb, preoperative creatinine, blood transfusion, and preoperative GFR of the healthy kidney. The multivariate Logistic regression analysis results showed that preoperative creatinine, GFR of the healthy kidney, and blood transfusion were independent risk factors for AKI. Moreover, The multivariate Logistic regression analysis of 52 patients with long-term renal insufficiency after surgery indicated that there were statistically significant differences in preoperative hydronephrosis, tumor size, preoperative GFR of the healthy kidney, and postoperative AKI.ConclusionFor patients with UTUC, the preoperative creatinine level is high, blood transfusion was given during or after procedure and the GFR of the healthy kidney is low, it is easy to have AKI in the short term after operation. In addition, there was no hydronephrosis before operation, the tumor size was small, the GFR of the healthy kidney was low before operation, AKI occurred after operation, the renal function was easy to deteriorate for a long time after operation. The above risk factors may aggravate renal function deterioration of these patients after surgery, resulting in the loss of the opportunity to continue treatment.